Taxonomy of Bethylus (Hymenoptera, Bethylidae) from China with description of nine new species - Wang, Chung-Hong; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2021)
Nine new species as well as a known species of Bethylus Latreille (Hymenoptera, Bethylidae) from China are described and illustrated: B. crassicapitis sp. nov., B. convexus sp. nov., B. gansensis sp. nov., B. glabricarinatus sp. nov., B. hunanensis sp. nov., B. incurvus sp. nov., B. ningxicus sp. nov., B. prolatus sp. nov., B. quadraticapitis sp. nov., and B. sinensis Xu, He & Terayama. A key to the known Chinese species is provided.